Most deprived Louisiana census tracts have higher hepatocellular carcinoma incidence and worse survival - Ratnapradipa, Kendra L.; Li, Tingting; Hsieh, Mei-Chin; Tenner, Laura; Peters, Edward S. (Frontiers in Oncology, 2024)
Background: Liver cancer incidence increased in the US from 1975 through 2015 with heterogeneous rates across subpopulations. Upstream or distal area-level factors impact liver cancer risks. Objective: To examine the association between area-level deprivation and hepatocellular carcinoma (HCC) incidence and survival. We also explored the association between area deprivation and treatment modalities. Methods: Louisiana Tumor Registry identified 4,151 adult patients diagnosed with malignant HCC from 2011-2020 and linked residential address to census tract (CT) level Area Deprivation Index (ADI) categorized into quartiles (Q1=least deprived). ANOVA examined the association between ADI quartile and CT age-adjusted incidence rate (AAIR) per 100,000. Chi-square tested the distribution of demographic and clinical characteristics across ADI quartiles. Kaplan-Meier and proportional hazard models evaluated survival by deprivation quartile. Results: Among the 1,084 CTs with incident HCC, the average (SD) AAIR was 8.02 (7.05) HCC cases per 100,000 population. ADI was observed to be associated with incidence, and the mean (SD) AAIR increased from 5.80 (4.75) in Q1 to 9.26 (7.88) in Q4. ADI was also associated with receipt of surgery (P < 0.01) and radiation (P < 0.01) but not chemotherapy (P = 0.15). However, among those who received chemotherapy, people living in the least deprived areas began treatment approximately 10 days sooner than those living in other quartiles. Q4 patients experienced the worst survival with median 247 (95% CI 211-290) days vs. Q1 at 474 (95% CI 407-547) days (P < 0.0001). Q4 had marginally poorer survival (HR 1.20, 1.05-1.37) than Q1 but the association became non-significant (HR 1.12, 0.96-1.30) when adjusted for rurality, liquor store density, sex, race/ethnicity, age, insurance, BMI, stage, Hepatitis diagnosis, and comorbidities. Conclusions: Increasing neighborhood (CT) deprivation (ADI) was observed to be associated with increased HCC incidence and poorer HCC survival. However, the association with poorer survival becomes attenuated after adjusting for putative confounders.